RELEVANSI PENDIDIKAN AGAMA KRISTEN DALAM PENGUATAN KOMPETENSI PELAYANAN GURU JEMAAT HKBP DI ERA DIGITAL - Manaek Simanungkalit (Jurnal Multidisipliner Kapalamada, 2025)
This study examines the relevance of Christian Religious Education in enhancing the competence of HKBP Congregation Teachers in the digital era. The study employs a qualitative literature review examinating of theories and previous research on service competence, church education, and the challenges of digital transformation. The findings indicate that the use of interactive digital media, Bible applications, and online forums enriches faith-based learning, making it more contextual and relevant for the congregation. Effective competence of HKBP Congregation Teachers encompasses mastery of theology, pedagogy, digital literacy, technical skills, professionalism, and spiritual maturity. Digital literacy supports the effectiveness of learning while simultaneously shaping character, moral responsibility, and adaptive management of pastoral ministry. Christian Religious Education plays a strategic role in equipping HKBP Congregation Teachers to use technology ethically, critically, and contextually, ensuring that church ministry remains relevant, adaptive to contemporary developments, and grounded in Christian values.